Variable Initial Swing Side and Prolonged Double Limb Support Represent Abnormalities of the First Three Steps of Gait Initiation in Patients with Parkinson’s Disease with Freezing of Gait - Okada, Yohei; Fukumoto, Takahiko; Takatori, Katsuhiko; Nagino, Koji; Hiraoka, Koichi (Frontiers in Neurology, 2011)
This study investigated abnormalities of the first three steps of gait initiation in patients with Parkinson’s disease without freezing of gait (PD-FOG) and investigated which abnormalities are related to FOG. Seven PD-FOG and 7 age-matched healthy controls performed self-generated or cue-triggered gait initiation. The center of pressure, heel contact positions, and spatiotemporal parameters were estimated from the vertical pressures on the surface of the force platform. Data for PD patients with FOG (PD+FOG) were cited from a previous study using a procedure similar to that used in the present study. Gait initiation was abnormal, and external cue normalized some abnormalities in PD-FOG. The initial swing side was fairly consistent among the trials in both PD-FOG and in healthy controls, although the initial swing side was inconsistent in PD+FOG. The duration of the first double limb support was the only parameter that depends on FOG severity and that was abnormal in PD+FOG but was not abnormal in PD-FOG. The variability of the initial swing side and prolonged first double limb support are abnormalities specifically related to FOG.